1990
DOI: 10.1034/j.1399-3054.1990.780409.x
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose and fructan metabolism of different wheat cultivars at chilling temperatures

Abstract: 1990. Suerose and fruetan metabolism of different wheat cultivars at chilling temperatures. -Physiol. Plant. 78; 554-559.Four wheat (Tritieum aestivum L.) varieties cultivated in different climates from subtropics to North Patagonia were used to study sucrose and fructan metabolism in plants when submitted to a cold period. Higher levels of sugars were found in the more cold tolerant cultivars. Sucrose synthase (EC 2.4.1.13) and sucrose phosphate synthase (EC 2.4.1.14) activities showed a 2-3 fold increase whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 9 publications
4
57
1
Order By: Relevance
“…The DP of fructooligosaccharides in young vegetative wheat seedlings is low (Fig. 4) as described by Bancal & Gaudillere (1989) and Tognetti et al (1990).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DP of fructooligosaccharides in young vegetative wheat seedlings is low (Fig. 4) as described by Bancal & Gaudillere (1989) and Tognetti et al (1990).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of phosphorylated substrate causes a retarded glycolysis in spite of Numerous studies provide direct or indirect evidence linking fructan metabolism to environmental stress (Archbold, 1938;Hendry, 1987;Pollock & Cairns, 1991). The relationship between fructans and the response of plants to low temperature has often been described (Wagner, Wiemken & Matile, 1986;Tognetti et al, 1990). However, whether fructans are directly involved in the mechanism of cold adaptation is still debatable because their accumulation may be the result of an increased content of sucrose for very difTerent reasons (Wagner, Keller & Wiemken, 1983;Cairns & Pollock, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be a consequence of the increase of sucrose possibly due to the enhancement of the activity of sucrose synthesizing enzymes at low temperature. Indeed, in wheat it was observed that sucrose phosphate synthase and sucrose synthase increase in plants stored at low temperatures (Calderon & Pontis 1985, Salerno et al 1989, Tognetti et al1989, 1990.…”
Section: Resultsmentioning
confidence: 99%
“…Also, several species of Asteraceae, as exemplified by chicory (Cichorium intybus L.), accumulate fructans of low degree of polymerization (DP) when exposed to chilling temperatures ( Van den Ende et al 1996). However, Tognetti et al (1990) pointed out that the role of fructan in cold acclimation remains an open question since its accumulation seems to be the result of sucrose accumulation (Wagner et al 1983, Cairns & Pollock 1988, Pollock & Cairns 1991 rather than the low temperature per se.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates were extracted in boiling alkaline water as previously reported (Tognetti et al, 1990), except that dry tissue was used. Bound fructose was determined by the TBA method.…”
Section: Extraction and Determination Of Sugarsmentioning
confidence: 99%